A Phosphinine‐Derived 1‐Phospha‐7‐Bora‐Norbornadiene: Frustrated Lewis Pair Type Activation of Triple Bonds. Issue 35 (29th May 2020) - Leitl, Julia; Jupp, Andrew R.; Habraken, Evi R. M.; Streitferdt, Verena; Coburger, Peter; Scott, Daniel J.; Gschwind, Ruth M.; Müller, Christian; Slootweg, J. Chris; Wolf, Robert
Abstract: Salt metathesis of 1‐methyl‐2, 4, 6‐triphenylphosphacyclohexadienyl lithium and chlorobis(pentafluorophenyl)borane affords a 1‐phospha‐7‐bora‐norbornadiene derivative 2 . The C≡N triple bonds of nitriles insert into the P−B bond of 2 with concomitant C−B bond cleavage, whereas the C≡C bonds of phenylacetylenes react with 2 to form λ 4 ‐phosphabarrelenes. Even though 2 must formally be regarded as a classical Lewis adduct, the C≡N and C≡C activation processes observed (and the mild conditions under which they occur) are reminiscent of the reactivity of frustrated Lewis pairs. Indeed, NMR and computational studies give insight into the mechanism of the reactions and reveal the labile nature of the phosphorus–boron bond in 2, which is also suggested by detailed NMR spectroscopic studies on this compound. Nitrile insertion is thus preceded by ring opening of the bicycle of 2 through P−B bond splitting with a low energy barrier. By contrast, the reaction with alkynes involves formation of a reactive zwitterionic methylphosphininium borate intermediate, which readily undergoes alkyne 1, 4‐addition. Abstract : Just like an FLP : A hetero‐norbornadiene incorporating phosphorus and boron atoms is accessible by a facile salt metathesis procedure. Although this compound represents a classical Lewis acid–base adduct, its reactivity is reminiscent of frustrated Lewis pairs. Reactions with nitriles and alkynes afford unusual insertion and 1, 4‐addition products. In both cases, reversible P−B bond dissociation is of key mechanistic significance.